Analytical Study of Schalors of Darul Uloom Haqqania and their Books on Jurisprudential Issues - Islam, Faiz ul; Ullah, Israr; Hammad, Muhammad (sourcecoder, 2023)
In this tempting age, new problem are arising. And the industrial and intellectual revolution that has created so many problems, solving these problems is a difficult and arduous task. It is the responsibility of the scholars to solve these difficult and difficult task.And they are the once who are able to find the right solution to these problem. Therefore the scholars of every age and the people of ifta have solved the problem of their respective area. In the present have also numerous such efforts are being made for these issues. And the Fuzala of jamia Haqqania Akorha khattak is an important roles of solving these jurisprudential issues.In Pakistan much work has been done in the field of jurisprudence .And great scholars have written numerous work on jurisprudential issues. But the Haqqania University of Akora Khattak also has a lot of services. But the services that we are going to mention today .they are about the authorship of jurisprudential issues. And an Analysis review on those jurisprudential issues will be presented.